2013
DOI: 10.1167/iovs.12-11049
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Promotes Apoptosis and Differentiation in Photoreceptors by Activating the P38 MAP Kinase Pathway

Abstract: PURPOSE. Retinoic acid (RA) has a critical role during development of the retina. We investigated RA effects on photoreceptor apoptosis and differentiation, and the intracellular pathways involved.METHODS. Rat retinal neuronal cultures were supplemented with RA with or without docosahexaenoic acid (DHA), a photoreceptor survival factor, and photoreceptor apoptosis and differentiation were evaluated at different times of development. To investigate the intracellular pathways activated by RA, the levels of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…However, promoter analysis suggest that there is no typical retinoic acid response elements (RARE) located in the proximal promoter of Ape/Ref-1. It has been reported that noncanonical actions of ATRA including the activation of mitogen-activated protein kinase (MAPK) pathways in a variety of cancer cells [29], [30]. In this study, we found that ATRA treatment activated p38 and MSK (mitogen- and stress-activated protein kinase) kinases in a dose-dependent fashion ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…However, promoter analysis suggest that there is no typical retinoic acid response elements (RARE) located in the proximal promoter of Ape/Ref-1. It has been reported that noncanonical actions of ATRA including the activation of mitogen-activated protein kinase (MAPK) pathways in a variety of cancer cells [29], [30]. In this study, we found that ATRA treatment activated p38 and MSK (mitogen- and stress-activated protein kinase) kinases in a dose-dependent fashion ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…Excess ROS generation and AA release play essential roles in the initiation of apoptosis in platelets. 21, 39 As p38/cPLA 2 is involved in the regulation of nucleated cell apoptosis 40, 41, 42, 43 and the possible involvement of p38/cPLA 2 in the induction of platelet apoptotic events is not known, we compared the mechanism of p38/cPLA 2 -mediated signaling induced by platelet agonists and ABT-737.…”
mentioning
confidence: 99%
“…Significantly fewer cells were seen to undergo PCD between E9 and E14 after RARB knockdown, arguing against a sensitizing effect of RA signaling in the CG, at least via RARβ. However, another recent study revealed that in retinal neuron cultures, RA selectively increases apoptosis in photoreceptors, when applied while cells still proliferated; regardless of the developmental stage although, RA promoted photoreceptor differentiation, shown by the expression of opsins and neurite outgrowth (De Genaro et al, ).…”
Section: Discussionmentioning
confidence: 99%